Tax and Transfer Policies and the Female Labor Supply in the EU - Klára Kalíšková (Institute for the Study of Labor (IZA), 2015)
This study contributes to the female labor supply responsiveness literature by measuring the effect of tax-benefit policies on female labor supply based on a broad sample of 26 European countries in 2005-2010. The tax-benefit microsimulation model EUROMOD is used to calculate a measure of work incentives at the extensive margin the participation tax rate, which is then used as the main explanatory variable in a female employment equation. This allows me to deal with the endogeneity of income in a new way by using a simulated instrumental variable based on a fixed EU-wide sample of women. Results suggest that a 10 percentage point increase in the participation tax rate decreases the female employment probability by 2 percentage points. The effect is higher for single mothers, for women in the middle of the skills distribution, and in countries that have lower rates of female employment.
Keywords: C25; H24; H31; J22; 330; female labor supply; tax and benefit system; Europe; instrumental variable